2013
DOI: 10.1111/gcb.12305
|View full text |Cite
|
Sign up to set email alerts
|

Soil organic carbon dust emission: an omitted global source of atmospheric CO2

Abstract: Soil erosion redistributes soil organic carbon (SOC) within terrestrial ecosystems, to the atmosphere and oceans. Dust export is an essential component of the carbon (C) and carbon dioxide (CO(2)) budget because wind erosion contributes to the C cycle by removing selectively SOC from vast areas and transporting C dust quickly offshore; augmenting the net loss of C from terrestrial systems. However, the contribution of wind erosion to rates of C release and sequestration is poorly understood. Here, we describe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 26 publications
1
42
0
Order By: Relevance
“…Wind erosion is one of the most important sources of uncertainty in terrestrial C accounting. Recent research on SOC redistribution within the landscape greatly improves our understanding on erosion's impact (Chappell et al, ; Van Oost et al, ; Wang et al, ). However, we still lack the basic field observations to constrain the causes, magnitudes, and consequences of soil erosion in the C cycle at the site level.…”
Section: Discussionmentioning
confidence: 99%
“…Wind erosion is one of the most important sources of uncertainty in terrestrial C accounting. Recent research on SOC redistribution within the landscape greatly improves our understanding on erosion's impact (Chappell et al, ; Van Oost et al, ; Wang et al, ). However, we still lack the basic field observations to constrain the causes, magnitudes, and consequences of soil erosion in the C cycle at the site level.…”
Section: Discussionmentioning
confidence: 99%
“…A well-established dust emission model was used to show that between 2000 and 2011 mean dust (< 22 μm) emission was 1.34 TgC/year and 0.11 TgC/year for rangeland and agricultural Australia, respectively [36]. Despite smaller SOC dust emission and SOC contents than agricultural Australia, the largest loss of SOC dust emission is from rangeland Australia because of the large area affected by wind erosion and dust emission.…”
Section: Soil Erosion Still Remains a Major Threat To Soil Securitymentioning
confidence: 99%
“…We account for all erosion processes (wind, water and tillage), specifically including wind erosion and dust emission, which has the potential to preferentially remove SOC rapidly from terrestrial ecosystems (Webb et al, 2012Chappell et al, 2013). Our estimates at the landscape or "catchment" scale (e.g.…”
Section: A Chappell Et Al: Australian Net (1950s-1990) Soil Organicmentioning
confidence: 99%
“…193) suggested that a good approximation to the enrichment ratio is based on a comparison of the particle size composition of the eroded material with that of the topsoil. Chappell et al (2013) recently produced a map of SOC enrichment in dust for Australia by assuming that SOC enrichment is proportional to the enrichment of soil fines, estimated from a physically based model of particle size selectivity:…”
Section: Carbon Enrichment By Size Selective Erosionmentioning
confidence: 99%